Yogic peace education : theory and practice - Standish, Katerina; Joyce, Janine M., 1965- (McFarland & Company, Inc., Publishers, 2017)
"This accessible introduction to peace education and yogic science provides a toolkit to help bring contemplative peacebuilding (intervention to stop harm) practices to the classroom and community center. The latest research is presented alongside personal reflections of teachers and facilitators. Preparatory exercises and practices are included, along with creative activities for emotional grounding and stress management"--